EFEKTIVITAS PENGGUNAAN MODEL ROUND TABLE DALAM MENINGKATKAN HASIL BELAJAR PPKN SISWA KELAS X - Ahmad Fadhilah Suandi; Rum Rosyid; Ika Rahmatika (Universitas Tanjungpura, 2019)
AbstractThis research aims to determine the effectiveness of using a round-table learning model to improve learning outcomes of 10th-grade Social Science 1 students in SMAN 2 Nanga Pinoh. This research used an experimental method in the form of pre-experimental research with